Literature review on type-2 fuzzy set theory - De, Arnab Kumar; Chakraborty, Debjani; Biswas, Animesh (Soft computing (Berlin, Germany), 2022)
Type-2 fuzzy sets possess higher capability of capturing uncertainties than ordinary fuzzy sets due to the presence of secondary membership degree. As a consequence, type-2 fuzzy set has remarkably progressed as a promising tool for dealing uncertainties in both theoretical as well as practical perspectives of various domains, like engineering, social sciences, arts and humanities, computer sciences, medical sciences, physical sciences, business and management, as well as in other areas. In this paper, a comprehensive literature survey on type-2 fuzzy set theory is presented. With the help of graphical representations, it is elaborately explained how type-2 fuzzy sets are gradually attracting the researchers years after years since its initiation. This article explores on the subject areas on which type-2 fuzzy sets have already established their potentiality to tackle imprecise information. Also, various extensions and developments of type-2 fuzzy sets have been presented in a systematic manner. Finally, future research directions of type-2 fuzzy set theory have been discussed.